Strongly vs. weakly coupled in-medium showers: energy stopping in large-N f QED - Peter Arnold; Omar Elgedawy; Shahin Iqbal (Journal of High Energy Physics)
Abstract Inside a medium, showers originating from a very high-energy particle may develop via medium-induced splitting processes such as hard bremsstrahlung or pair production. During shower development, two consecutive splittings sometimes overlap quantum mechanically, so that they cannot be treated independently. Some of these effects can be absorbed into an effective value of a medium parameter known as q ̂ $$ \hat{q} $$ . Previous calculations (with certain simplifying assumptions) have found that, after adjusting the value of q ̂ $$ \hat{q} $$ , the leftover effect of overlapping splittings is quite small for purely gluonic large-N c showers but is very much larger for large-N f QED showers, at comparable values of Nα. Those works did not quite make for apples-to-apples comparisons: the gluon shower work investigated energy deposition from a gluon-initiated shower, whereas the QED work investigated charge-deposition from an electron-initiated shower. As a first step to tighten up the comparison, this paper investigates energy deposition in the QED case. Along the way, we develop a framework that should be useful in the future to explore whether the very small effect of overlapping splitting in purely gluonic showers is an artifact of having ignored quarks.